Effectiveness of STEM-Based Project-Based Learning in Enhancing Senior High School Students’ Scientific Literacy - Ainun Mardiyah Lubis; Yus Mochamad Cholily; Rr. Eko Susetyarini; Elly Purwanti; Yulia Anita; Nor Mita Ika Saputri; Elisa; Dikmatul Qoimah (Postgraduate, University of Mataram, 2026)
The purpose of this study was to examine the effectiveness of the STEM (science, technology, engineering, and mathematics)-based Project-Based Learning (PjBL) model in improving senior high school students’ scientific literacy. This study employed a quasi-experimental method with a pre-test and post-test nonequivalent control group design and was conducted at SMA Negeri 5 Padangsidimpuan. The research involved two classes consisting of 35 students each: an experimental class taught using STEM-based PjBL and a control class taught using conventional learning. Scientific literacy was measured using an essay test, while students’ attitudes toward science were assessed through a questionnaire. The results of the independent samples t-test showed no significant difference in students’ initial abilities (sig. = 0.064 > 0.05). However, the post-test results indicated a significant difference between the two groups (sig. = 0.000 < 0.05), with the experimental class achieving a higher mean score. In addition, students’ attitudes toward science in the experimental class were categorized as good to very good. These findings indicate that STEM-based Project-Based Learning is effective in enhancing students’ scientific literacy.